Level of health behaviours of HCV infected patients treated with dialysotherapy - Lidia Sierpińska; Karolina Lis (Kazimierz Wielki University, 2019)
Introduction. Hepatitis C virus (HCV) infection is one of the greatest epidemiological risks worldwide (3% infected globally). Dialysis patients are the group at high risk of infections transmitted via blood, are often infected with HCV virus, and suffer from acute or chronic hepatitis. Anti-health behaviours enhance the process of liver fibrosis. The objective of the study was recognition of the level of health behaviours in HCV-infected haemodialysis patients.  Materials and Method. The study included 149 adult patients on dialysis infected with HCV, hospitalized in two dialysotherapy centres: the Military Medical Institute and Clinical Hospital in Warsaw. In the study there also participated family members and acquaintances of students of the Higher School in Radom. The study was conducted during the first half of 2017 by a diagnostic survey, using research instrument Health Behaviours Inventory (HBI) according to Z. Juczyński. The questionnaire concerned: eating habits, prophylactic behaviours, everyday health practice, and positive psychological attitude. Results. 73.8% of respondents presented a high level of health behaviours (7-10 sten scores), mediocre - 19.5% (5-6 sten scores), and low - 6.7% (1-4 sten scores). The highest mean value evidencing health promoting life style of the patients was observed with respect to prophylactic behaviours (4.0±0.4), while eating habits and health practices were on the level 3.9±0.4-0.5. The lowest value indicating the least pro-health behaviours concerned positive psychological attitude (3.7±0.4).  Conclusions. The overall rate of health behaviours of dialysed HCV patients was high. The dominant category was prophylactic behaviours, whereas the lowest results were obtained with respect to positive psychological attitude. The respondents infected with HCV for longer than 10 years, mainly males, those aged 60-84, with primary vocational education, living in rural areas, and non-active occupationally, had the greatest needs for psychotherapy. It is necessary to provide psychological support for dialysis patients infected with HCV.